Oral Transmission to Symbolic Capital: Pragmatic Analysis of Teacher-Student Interaction in Tasmīʻ Ḥadīth Tradition - Ririn Rizkiya Utami; Alauddin Shahih (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
The interaction between teachers (kiai) and students (santri) has always played a crucial role in Islamic education, particularly within the tasmīʻ ḥadīth tradition in pesantren, where knowledge is transmitted both orally and symbolically. This oral interaction not only represents a pedagogical process but also serves as a social mechanism through which authority, respect, and scholarly values are reproduced. This study aims to examine the pragmatic dimensions of communication during the tasmīʻ ḥadīth performance and to interpret how these interactions generate symbolic capital within the pesantren context. The focus of this study is directed toward how utterances, corrections, and verbal responses between teachers and students construct symbolic power relations and reproduce religious values within the Islamic scholarly tradition. This research employs a qualitative approach using participatory observation and in-depth interviews. Data were collected through observations conducted at a pesantren in East Lombok. Data analysis was carried out by identifying speech acts, politeness strategies, and forms of symbolic recognition that emerge during the tasmīʻ process. The findings show that oral interaction between teachers and students functions not only as a means of transmitting religious knowledge but also as a medium for constructing symbolic capital in the form of scholarly legitimacy, hierarchical respect, and the internalization of pious values. This study offers a new contribution by integrating pragmatic analysis and the theory of symbolic capital within the context of the tasmīʻ tradition, which has rarely been explored from an interdisciplinary perspective.